Pengaruh Nilai Radius terhadap Pemilihan Zona Optimal Protokol ZRP (Zone Routing Protocol) pada Lingkungan MANET (Mobile Adhoc Network) - Daniel H. Simatupang; Primantara Hari Trisnawan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
A manet network is made up of moving nodes (mobile), each node that can establish communication with another without requiring a constant channel or template for that matter. The characteristic of manet is self-indulgence in which there is no need for a definition of infrastructure first. The kinds of protocols available in manet vary so much as proactive, reactive and hybrid protocols. The formation of zones depends on the manually designated radius values, the radius values has a significant share in the routing process. The observation of radius values affects the performance of ZRP's routing protocol using an NS-2 simulator. With a variation in number of nodes 20, 40, 60 and 80, variations in value radius 2, 3, 4 and 5 at area 1000m x 1000m using Random Way Point movements. Based on testing of ZRP's routing protocol with the packet delivery ratio (PDR), normalized routing load (NRL), end-to-end delay, throughput parameters with value radius 2 show better results in all test scenario for test parameters. For the parameters of the convergence time test, the value of radius 4 shows better on the entire test scenario.